Health care gap affects 20% of United States population: Transition from pediatric to adult health care - Margaret McManus; Patience White; Annie Schmidt; Michael Barr; Carolyn Langer; Kevin Barger; Allysa Ware (Elsevier, 2020)
Transition-aged youth and young adults, ages 12 to 26, represent almost 20% of the US population, and an estimated 25%-35% have one or more chronic conditions. The vast majority of youth with and without special health care needs do not receive the necessary and professionally recommended services to transition from pediatric to adult care. Without adequate support during this transition, youth and young adults face an increased risk of adverse outcomes. To accelerate adoption of recommended transition processes in both pediatric and adult systems of care, the authors offer a series of implementation, payment, and research options that are consistent with clinical guidelines from the American Academy of Pediatrics, American Academy of Family Physicians, and American College of Physicians.